Korelasi Literasi AI terhadap Kemampuan Matematis Mahasiswa di Era Artificial Intelligence - Dea Permita Sari; Tiara Cika Utami; Nadia Zahra Afifah; Netriwati; Indah Resti Ayunisuri (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2026)
This study aims to examine the level of Artificial Intelligence literacy among university students, analyze their mathematical problem-solving skills, and identify the relationship and contribution of Artificial Intelligence literacy to those skills. The research employed a quantitative approach with a correlational design to investigate the relationship between the variables studied. The participants consisted of 50 students from the Mathematics Education Study Program at Raden Intan State Islamic University of Lampung. Data were collected through an AI literacy questionnaire and a mathematical problem-solving test. The data were analyzed using normality and linearity tests, Pearson correlation analysis, and simple linear regression with SPSS. The results indicated that the data were normally distributed and met the assumption of linearity. Based on the correlation analysis, there was a significant and very strong relationship between AI literacy and mathematical problem-solving skills. This finding was reflected in the correlation coefficient of 0.858 with a significance value of 0.000. In addition, the regression analysis showed that Artificial Intelligence literacy contributed 73.7% to students’ mathematical problem-solving skills. These findings suggest that Artificial Intelligence literacy plays an important role in supporting students’ mathematical thinking abilities in the digital era